2019
DOI: 10.29252/wjps.8.1.51
|View full text |Cite
|
Sign up to set email alerts
|

The Healing Effect of Plantago Major and Aloe Vera Mixture in Excisional Full Thickness Skin Wounds: Stereological Study

Abstract: BACKGROUNDPrevious studies indicated that both Plantago major and Aloe vera have anti-inflammatory, tissue regeneration, antioxidant, and immune-stimulatory effects. It is assumed that a mixture of these two herbal medicines may provide a potent material in treatment of skin wound injuries. Therefore, in this study we investigated the effects of Plantago major and Aloe vera mixture in the process of wound healing in rat models according to stereological parameters. METHODSIn an experiential study, 36 male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…This finding shows that the administration of laser can lessen the cytotoxicity impact of high concentrations of P. major, indicating an effective synergistic effect of laser and P. major combination. This synergistic effect of combination therapy is in consistent with a recent study, which reported that the mixture of P. major and aloe vera accelerates the process of wound closure by inducing fibroblast proliferation and increasing collagen bundles 22 .…”
Section: Discussionsupporting
confidence: 91%
“…This finding shows that the administration of laser can lessen the cytotoxicity impact of high concentrations of P. major, indicating an effective synergistic effect of laser and P. major combination. This synergistic effect of combination therapy is in consistent with a recent study, which reported that the mixture of P. major and aloe vera accelerates the process of wound closure by inducing fibroblast proliferation and increasing collagen bundles 22 .…”
Section: Discussionsupporting
confidence: 91%
“…ey reported that the P. major water extract, especially with 50% concentration, could be a suitable substitute for sulfadiazine silver in burn injury healing and also suggested further studies in humans [20]. Another study demonstrated that the mixture of P. major and Aloe vera gel speeded up the wound recovery time as the result of an increase in the density of vessels, broblasts, and collagen bers in the wound site [21]. Furthermore, in a human study, this gel was found to have signi cantly reduced the ulcer surface of diabetic foot ulcers [22].…”
Section: Discussionmentioning
confidence: 95%
“…Wound healing is one of the most fundamental issues that human beings have faced since the beginning of creation. Numerous drugs and ointments are used to repair open wounds, each of which has several drawbacks, limitations, and side effects (3)(4)(5). Today, the importance of healing is due to the high prevalence of wounds in human and animal communities.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a complex process that causes restoration of structural and functional integrity after injury (2). Wound healing involves coordinated repair responses of blood cells, extracellular matrix, and parenchymal cells that occur after surgery or traumatic injury to the body (3). Wound healing has long been considered one of the most important issues in surgery.…”
Section: Introductionmentioning
confidence: 99%